Recent Research into the History of Early Shi'ism - Gleave, Robert (History compass, 2009)
This article examines some of the scholarship on early published in the last decade in English, French and German. Particular emphasis is paid to the emergence of the majority trend, its self-definition and the development of doctrinal unity. Any social or political history of early will inevitably be partial as the division between these categories of analysis and the intellectual development of dogma and doctrine is somewhat artificial when considering early Islam. The emergence of a dogmatic orthodoxy is linked with both the production of a distinctive identity and the subsequent or Twelver tradition of thought.